2014
DOI: 10.1186/s40510-014-0056-7
|View full text |Cite
|
Sign up to set email alerts
|

The short-term skeleto-dental effects of a new spring for the intrusion of maxillary posterior teeth in open bite patients

Abstract: BackgroundThe technology surrounding temporary skeletal anchorage devices has improved in leaps and bounds. However, no specific auxiliary exists for the intrusion of molars in conjunction with these devices and currently clinicians are forced to make do with available force delivery materials. A new intrusion auxiliary, the Sydney Intrusion Spring (SIS), was designed to facilitate intrusion without frequent need for reactivation or tissue irritation.MethodsThe subjects consisted of 16 adolescent patients (12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…For our treatment modalities for maxillary posterior tooth intrusion, the force magnitude (as low as 50 g per side) was lower than previously recommended (Table 1) [10–15]. …”
Section: Discussionmentioning
confidence: 65%
“…For our treatment modalities for maxillary posterior tooth intrusion, the force magnitude (as low as 50 g per side) was lower than previously recommended (Table 1) [10–15]. …”
Section: Discussionmentioning
confidence: 65%
“…A debate in the literature regarding the force magnitude required for effective skeletal anchoragesupported posterior segment intrusion has been reported. 17 Different authors used variable forces and reported different amounts of intrusion. The minimum intrusive force used was 50 g per side, 21 while the more commonly used forces ranged between 100 and 200 g. 13,14,22 On the other hand, Kato and Kato 23 suggested that a force of 100 g was insufficient for posterior segment intrusion and stated that increasing the force up to 300 g permitted progressive intrusion.…”
Section: Discussionmentioning
confidence: 99%
“…Later, a range of 200 to 400 g for segmental posterior intrusion was suggested. 24 Less commonly, heavier forces were used, ranging from 400 g 16 up to 500 g, [17][18][19] to achieve adequate amounts of intrusion. Since most of these studies used different methodologies, their results could not be compared directly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Miniscrews can also be used for anterior open bite treat ment. 14,15 Through the use of miniscrews for intrusion of the upper and lower posterior teeth, similar rates of mandibular autorotation can be achieved as miniplates. 16 However miniplates are more reliable compared to the miniscrews because of their distance from tooth roots.…”
Section: Discussionmentioning
confidence: 99%